2022
DOI: 10.1093/milmed/usab537
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Functional Motor Competence and Performance on the Army Combat Fitness Test in Army Reserve Officer Training Corps Cadets

Abstract: Introduction The development of functional motor competence (FMC; i.e., neuromuscular coordination and control required to meet a wide range of movement goals) is critical to long-term development of health- and performance-related physical capacities (e.g., muscular strength and power, muscular endurance, and aerobic endurance). Secular decline in FMC among U.S. children and adolescents presents current and future challenges for recruiting prospective military personnel to successfully perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These fitness measures were chosen to better predict combat readiness for modern battlefield demands, and the shift from the APFT to the ACFT demonstrates a change in physical readiness training doctrine that focuses on full-body muscle-strengthening activities and cardiovascular endurance in parallel. To date, research has identified that functional motor competence [ 19 ] and body composition [ 20 ] are significantly related to ACFT performance, yet, comparisons between physical activity behaviors and the expanded ACFT fitness domains are lacking for military personnel.…”
Section: Introductionmentioning
confidence: 99%
“…These fitness measures were chosen to better predict combat readiness for modern battlefield demands, and the shift from the APFT to the ACFT demonstrates a change in physical readiness training doctrine that focuses on full-body muscle-strengthening activities and cardiovascular endurance in parallel. To date, research has identified that functional motor competence [ 19 ] and body composition [ 20 ] are significantly related to ACFT performance, yet, comparisons between physical activity behaviors and the expanded ACFT fitness domains are lacking for military personnel.…”
Section: Introductionmentioning
confidence: 99%
“…The development of MC (i.e., neuromuscular coordination and control required to meet a wide range of movement goals) plays a critical role in the longterm development of health-and performance-related physical capacities (e.g., muscular strength and power, muscular endurance, and aerobic endurance. Previous research [38] examined the relationship between functional MC and physical military readiness among Army Reserve Officer Training Corps cadets. Results showed a strong correlation between functional MC and physical military readiness, with low levels of functional MC serving as a significant predictor of failure in the Army Reserve Officer Training Corps.…”
Section: Discussionmentioning
confidence: 99%
“…Product scores were also assessed for kicking (maximal speed) [ 43 , 44 ], overhand throwing (maximal speed) [ 43 , 44 ], and catching (number of successful catches; [ 45 ]). Throw and kick speed were completed by asking participants to throw or kick a ball as hard as they could at a wall 20 feet away.…”
Section: Methodsmentioning
confidence: 99%